A comparative study to evaluate endometrial aspiration using Karman’s cannula versus dilatation and curettage in cases of abnormal uterine bleeding - Tomar, Neetu Sangwan; Sandhu, Seerat; Mahipal, Supriya; Chaudhary, Abhimanyu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Abnormal uterine bleeding (AUB) is defined as any variation from the normal menstrual cycle such as changes in regularity, frequency, duration of flow or amount of flow. Objective of this study was to compare the adequacy and diagnostic accuracy of endometrial aspiration using Karman’s cannula versus dilatation and curettage in women with abnormal uterine bleeding. Methods: This prospective study was conducted on 250 women with AUB in age group of more than 40 years. In all patients, endometrial aspiration was done with manual vacuum aspiration (MVA) syringe attached to 4 mm Karman’s cannula without anesthesia. The sample was collected in a bottle containing formalin and was labelled as sample A. After that, intracervical local anesthesia (1% Xylocaine) was given and cervix was dilated and scrapping of endometrial lining with sharp curette was done. The sample was also collected in a bottle containing formalin and was labelled as sample B. Both the samples A and B were sent for histopathology. The histopathology report of aspiration was compared with that of dilatation and curettage sample. Results: Endometrial aspiration biopsy had sensitivity of 92.3%, specificity of 100%, positive predictive value of 100% and negative predictive value of 99.56% for diagnosis of endometrial pathology while considering D and C gold standard. The sample adequacy of endometrial aspiration was 98.8% as compared to dilatation and curettage (98%). Conclusions: Present study showed that endometrial aspiration biopsy is an alternate to traditional dilatation and curettage in diagnosing endometrial pathologies in women with abnormal uterine bleeding.